Isolation of ergosterol peroxide and its reversion to ergosterol in the pathogenic fungus Sporothrix schenckii - Da Graça Sgarbi, Diana Bridon; Da Silva, Antonio Jorge Ribeiro; Carlos, Iracilda Zeppone [UNESP]; Silva, Célio Lopes; Angluster, Jayme; Alviano, Celuta Sales (Springer Nature, 1997)
Ergosterol peroxide, a presumed product of the H2O2-dependent enzymatic oxidation of ergosterol, has been isolated from yeast from yeast forms of the pathogenic fungus Sporothrix schenckii. The substance, which may have a role in fungal virulence, has been characterized mainly using spectroscopic methods (1H and 13C nuclear magnetic resonance and high resolution mass spectra). The purified compound showed a molecular formula of C28H44O3, displaying characteristic features of epidioxy sterols and was reverted to ergosterol when submitted to S. schenckii enzymatic extract.
Keywords: Epidioxy sterol; Reactive oxygen species; Sporothrix schenckii; antineoplastic agent; drug derivative; ergosterol; ergosterol 5,8 peroxide; ergosterol-5,8-peroxide; chemistry; isolation and purification; metabolism; nuclear magnetic resonance spectroscopy; Sporothrix; thin layer chromatography; Antineoplastic Agents; Chromatography, Thin Layer; Ergosterol; Magnetic Resonance Spectroscopy; Fungi